Chemical communication in free-ranging gray brocket deer (Mazama gouazoubira) - Juliano André Bogoni; Rafael Barbizan Sühs; Maurício Eduardo Graipel; Nivaldo Peroni (Biotemas)
Chemical communication is intensely used by deer, especially scent-marking behaviors, with territory marking mainly made by males. This work presents several video recordings of at least two gray brockets (male and female) chemically communicating via scent marks. Video recordings demonstrate multiple depositions of feces and urine by the animals, probably for the development of intrasexual interaction and, secondarily, territorial marks. The chemical communication observed is possibly related to reproduction or intraspecific competition for resources. These territorial marks are particularly important for avoiding intraspecific competition for resources and sexual partners.